1996
DOI: 10.1007/bf01849540
|View full text |Cite
|
Sign up to set email alerts
|

Post-abortion complications after interruption of pregnancy with misoprostol

Abstract: The high incidence of abortion in Brazil and the increased use of misoprostol among women having clandestine/unsafe abortions has led to an interest in evaluating whether there is an association between the use of misoprostol and the incidence of septic complications post-abortion. To test this association, a retrospective cohort study was conducted with 1840 women treated post-abortion at the Instituto Materno-Infantil de Pernambuco (IMIP) between 1988 and 1992. Incidence of infection (4.2%) was lower in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 14 publications
1
22
0
7
Order By: Relevance
“…Compared to other techniques used to induce abortions clandestinely, medical methods appear to be safer and associated with fewer complications. [7][8][9] As a result, mortality from unsafe abortions may have decreased in the region. This has been seen in several countries, including Peru and Brazil, 7,9,10 and is suspected more widely by public health experts.…”
mentioning
confidence: 99%
“…Compared to other techniques used to induce abortions clandestinely, medical methods appear to be safer and associated with fewer complications. [7][8][9] As a result, mortality from unsafe abortions may have decreased in the region. This has been seen in several countries, including Peru and Brazil, 7,9,10 and is suspected more widely by public health experts.…”
mentioning
confidence: 99%
“…This makes it important for women to be able to receive adequate post-abortion care for such complications, which can help to reduce the morbidity and mortality from unsafe abortion if accessible in a timely manner. 5 Studies carried out in Latin America 6 indicate that the increase in the self-use of misoprostol for medical abortion is related to a decrease in serious complications and maternal mortality and morbidity caused by unsafe abortions with other methods. This article shows how Safe Abortion Information Hotlines are one means of allowing women to obtain reliable information about medical abortion.…”
Section: The Global Impact Of Unsafe Abortionmentioning
confidence: 99%
“…17 Studies show that in the last decade, in Latin American countries, a relationship exists between access to misoprostol and a reduction in hospital stays for complications of unsafe abortion. 6 These studies attribute at least part of the reasons to the wide distribution and popularity that misoprostol has gained, ‡ especially in urban populations.…”
Section: Medical Abortion In Legally Restrictive Contextsmentioning
confidence: 99%
“…In the area of post-abortion care, research in Brazil demonstrated the cost savings of introducing MVA in settings where dilatation and curettage (D&C) was the norm, especially when MVA is performed on an outpatient basis under local anaesthesia. 7 Similarly, a recent study from Nigeria found that out-of-pocket costs were higher for women who developed serious complications after an abortion outside of the hospital compared to those who had less severe or no complications. 10 Yet this study also reported that charges for D&C were only slightly higher than those for MVA, 8 even though outpatient MVA should be less costly than inpatient D&C. 6 The aim of this study was to estimate the costs incurred by the health care system associated with the treatment of incomplete abortion and other abortion complications due to unsafe abortion in Mexico City prior to reform of the abortion law.…”
mentioning
confidence: 97%
“…This has been documented in Brazil, where, as misoprostol use increased, a corresponding reduction in abortion-related complications was observed. 7 A recent review of death certificates in two districts in Mexico found no deaths that were suspected to be related to first trimester abortion procedures. 8 Another study on the incidence of abortion in Mexico found that the severity of abortion-related complications decreased between 1990 and 2006.…”
mentioning
confidence: 99%